The determinants of firm's sustainability performance: a systematic review - Dwi Kristina Anggita; Jaharuddin, Nor Siah; Mansor, Zuraina (Herald Academic Ltd, 2024)
Amidst the environmental issues facing the global business landscape, more companies are adopting sustainability as a fundamental component of their organizational strategy. Therefore, it is essential to investigate the critical success factors that drive corporate sustainability by pursuing green innovation. This study explores the critical success factors that affect sustainable firm performance and investigates the impact of an organization's green innovations on sustainable firm performance. The method employed was bibliographic instruments, which involved creating a detailed list of keywords to search for the article online using Google Chrome. There were 55 publications published between 2018 and 2023 from Scopus for the final review. Identified critical areas for examination and made recommendations for future research to accelerate progress toward sustainable performance. This study improves the current body of knowledge by pinpointing the essential vital success variables and the influence of green innovation on promoting corporate sustainability. It also promotes future research that follows high-quality criteria.